THE INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE AND PERSONAL INCOME ON FINANCIAL MANAGEMENT IN GENERATION Z IN SOUTH JAKARTA : Pengaruh Literasi Keuangan, Lifestyle, dan Personal Income Terhadap Pengelolaan Keuangan Generasi Z di Jakarta Selatan - MIA WAHYU NURAINI; Theresia Priadani; Yunus Handoko (SOSIOEDUKASI, 2025)
ABSTRACT This study aims to determine and analyze the influence of financial literacy, lifestyle, and personal income on financial management among Generation Z in South Jakarta. Study results show that digital developments have made Generation Z more open to accessing information, thereby improving financial management. However, other studies indicate that Generation Z has limited ability in financial management. Therefore, the topic of financial management becomes interesting to explore. South Jakarta was chosen as the research object because its population is predominantly Generation Z. In addition, South Jakarta is also a hub for youth trends in various aspects, particularly lifestyle, fashion, and social gathering spots. The quantitative research method used is non-probability with a random sampling technique, and the sample size was determined using the Cooper and Emory formula, totaling 100 respondents. Data were collected through questionnaires and analyzed using SPSS 27. The research results indicate that financial literacy has an influence on financial management. Lifestyle also has a proven influence on financial management. Personal income has an influence on financial management as well. Simultaneous testing results also show that financial literacy, lifestyle, and personal income have a collective influence on financial management.